SERANGAN HAMA Spodoptera frugiperda (Lepidotera:Noctuidae) PADA PERTANAMAN JAGUNG DI NUSA TENGGARA TIMUR - Pu'u, Yustina Maria Silvia Wonga (Agriculture Faculty of Flores University, 2025)
This study aims to analyse the damage caused by Spodoptera frugiperda to maize crops in East Nusa Tenggara (NT1T). The study was conducted on three islands, namely Timor, Flores, and Sumba. The observation method used was the Scouting system. Samples were taken using a ‘W’ pattern approach. The percentage of infested plants was analysed by dividing the total number of infested plants by the number of plants observed and multiplying by 100%. Meanwhile, the intensity of infestation was calculated using the formula ? (ni x vi)/(NxV) x 100%. The results showed that the average S. frugiperda infestation on maize plants across all observation sites was 100%. The percentage of infested plants at all locations indicated that S. frugiperda had spread evenly throughout East Nusa Tenggara. Meanwhile, the highest average intensity of S. frugiperda attacks was in Tuatuka village at 83.52% and the lowest was in Wolofeo village at 22.11%. Affected corn plants showed characteristic symptoms, namely holes and transparency in the leaves, and larvae were found in the leaves and stems with sawdust-like traces of their gnawing.